MANAJEMEN INTEGRASI KURIKULUM DI MADRASAH TSANAWIYYAH QUDSIYYAH KUDUS - Ahmad Nidhomulhaq; Yuli Utanto; Dwi Cahyaningdyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the management process of curriculum integration between the Kemendikbud Curriculum, the Kemenag Curriculum, and the Salaf Curriculum at MTs Qudsiyyah Kudus. The main focus is on the planning, implementation, and evaluation processes of curriculum management in accordance with the National Education Standards (SNP). This research adopts a qualitative approach using a case study method. The findings indicate that curriculum integration management is carried out collaboratively between the madrasah and the pesantren, although challenges persist in aligning the traditional curriculum with the demands of the national curriculum. Adaptive and synergistic management strategies are required to ensure that curriculum integration enhances the quality of education and contributes to students' character development.